THE IMPROVING STUDENTS’ SPEAKING SKILL USING FLIPA CLIP MEDIA FOR THE FIRST-GRADER OF MA SUNAN AMPEL DAMPIT - Saiful Bahri; Norma Ita Sholichah (LP3M IAI Al-Qolam, 2025)
Sunan Ampel Dampit through the use of Flipa Clip media. The research began with observations of the challenges students face in expressing themselves verbally, often due to lack of confidence and fear of speaking in public. From the preliminary study results, it was found that students showed significant improvement after implementing Flipa Clip media in the learning process. This research used the Collaborative Classroom Action Research (CAR) method involving observation, interviews, and tests to collect data. The results showed that the use of Flipa Clip media increased motivation and participation of students in learning English, especially in speaking. Students became more creative and motivated to communicate ideas in English. From observations and tests, it was found that students using Flipa Clip media showed an average score increase from 75 to 88, indicating that they met the success criteria set by the researcher. This research provides practical contributions to educators and students in improving the quality of English language learning, particularly in speaking. The findings also suggest that the use of interactive media like Flipa Clip can be an effective strategy to overcome confidence issues and fear of public speaking. This research is expected to serve as a reference for future studies focusing on language development through multimedia approaches.